SEQUENTIALLY CONVERGENT MAPPINGS AND COMMON FIXED POINTS OF MAPPINGS IN 2-BANACH SPACES - Lukarevski, Martin; Malčeski, Samoil (Matematichki Bilten, 2016)
In the past few years, the classical results about the theory of fixed point are transmitted in 2-Banach spaces, defined by A. White (see [3] and [8]). Several generalizations of Kannan, Chatterjea and Koparde-Waghmode theorems are given in [1], [4], [5] and [7]. In this paper, several generalizations of already known theorems about common fixed points of mappings in 2-Banach spaces, are proven, by using the sequentially convergent mappings.